Percy Jackson & The Olympians: The Last Olympian-Book 5 - Riordan, Rick; Bernstein, Jesse 1976- (New York : Listening Library, 2009)
The long-awaited prophecy surrounding Percy Jackson's sixteenth birthday unfolds as he leads an army of young demigods to stop Kronos in his advance on New York City, while the Olympians struggle to contain the rampaging monster, Typhon.
Unabridged.
Compact discs.
Read by Jesse Bernstein.
Keywords: Children's audiobooks; Mythology, Greek -- Fiction; Fate and fatalism -- Fiction; Monsters -- Fiction; Animals, Mythical -- Fiction; Titans (Mythology) -- Fiction; Audiobooks